(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article examines the inclusion of modern technologies into translation process, particularly machine translation and CAT-tools. The paper addresses the benefits and drawbacks of the implementation of innovations and proposes possible ways to avoid negative consequences of machine intervention into translation.